Pegylated interferon α-2a versus standard interferon α-2a for treatment-naïve dialysis patients with chronic hepatitis C: a randomised study. Issue 4 (19th September 2007) - Liu, C-H; Liang, C-C; Lin, J-W; Chen, S-I; Tsai, H-B; Chang, C-S; Hung, P-H; Kao, J-H; Liu, C-J; Lai, M-Y; Chen, J-H; Chen, P-J; et al.
Abstract : Background: Chronic hepatitis C virus (HCV) infection is prevalent in dialysis patients, and standard interferon monotherapy is the current standard of care for such patients. Aim: To investigate whether pegylated interferon has a better therapeutic efficacy and safety profile than standard interferon in dialysis patients with chronic hepatitis C. Methods: 50 such patients were randomly assigned to receive either pegylated interferon α-2a 135 μg subcutaneously once per week or standard interferon α-2a 3 million units subcutaneously thrice per week for 24 weeks. The primary efficacy and safety end points were sustained virological response (SVR) by intention-to-treat analysis and treatment-related withdrawal rate during the study. Results: In univariate analysis, patients receiving pegylated interferon α-2a tended to have a higher sustained virological response (SVR) than those receiving standard interferon α-2a (48% vs 20%, p = 0.07). By using multivariate analysis, treatment with pegylated interferon α-2a (p = 0.02) and pretreatment HCV RNA level <800 000 IU/ml (p = 0.007) were independently predictive of an SVR. All patients failing to achieve a rapid virological response (RVR) could not achieve an SVR. In addition, patients receiving pegylated interferon α-2a had a significantly lower treatment-related withdrawal rate than those receiving standard interferon α-2a (0% vs 20%, p = 0.04). Conclusions: Pegylated interferon α-2a once weekly provides more effective and safer therapy than standard interferon α-2a thrice weekly for treatment-naïve dialysis patients with chronic hepatitis C.